Investigating Dissertations and Theses on Ethics in the Field of Education in Turkey - (:unkn) unknown (IGIAD-TURKISH ENTREPRENEURSHIP & BUSINESS ETHICS ASSOC, 2017)
The purpose of this study is to investigate dissertations and theses on ethics in the field of education in Turkey. In this descriptive study, the general scanning method was used, and dissertations and theses in the scope of this study were analyzed using the method of document analysis. In light of the data obtained from the Council of Higher Education's Thesis Center on February 27, 2017, there are 121 theses and dissertations in total in the field of education (108 master's theses and 13 doctoral dissertations). These were all examined through the scope of analysis according to type, year prepared, university conducted in, research design, stages, and the elements being questioned in the education system. The quantitative results indicate that the first graduate article on ethics was prepared in 1998, and the highest number of graduate papers on ethics belongs to the year 2014 with 19 studies. The graduate studies on ethics in the field of education were mostly conducted between 2007 and 2015, and the majority of these were master's theses. Most were also specified to use the descriptive survey design and quantitative model, and the most frequently questioned element in terms of ethics was school administrators in the dissertations and theses prepared in the field of education.
Keywords: Education; Ethics; Dissertation; Thesis; Thesis examination